Income and consumption of retirees: a cross-country comparison - Ryzhkova, Marina (Advances in computer science research)
This paper reports results of comparison of retirees' assets, incomes, and consumption expenditures among three countries (the UK, US and Russia). The analysis was conducted on the basis of official statistic reports and on the data of special government and public organizations. Our findings are the following. The decrease of income while aging is the common feature for every country. Retirees in the UK and US own assets the revenue from which helps them to overcome the reduction in income. But for Russian pensioners it is hard to get by with only social payments. Their main strategies are to continue working or to cut some expenditure. But still they have savings. As a result special marketing policies which should be oriented on old people are suggested.